2020
DOI: 10.1186/s13018-020-02024-7
|View full text |Cite|
|
Sign up to set email alerts
|

The feasibility of short-segment Schanz screw implanted in an oblique downward direction for the treatment of lumbar 1 burst fracture: a finite element analysis

Abstract: Background To evaluate the biomechanical properties of short-segment Schanz screw implanted in an oblique downward direction for the treatment of lumbar 1 burst fracture using a finite element analysis. Methods The Universal Spine System (USS) fixation model for adjacent upper and lower vertebrae (T12 and L2) of lumbar 1 vertebra burst fracture was established. During flexion/extension, lateral bending, and rotation, the screw stress and the displacement of bone defect area of the injured vertebrae were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[30] Furthermore, in tests using synthetic spines, a maximum non-destructive axial compression of 350 N is recommended. [31,32] Accordingly, we chose 325 N which corresponded to a 3 mm displacement. The first set of experiments were carried out using a synthetic biomimetic lumbar spine model (Sawbones, WA, USA) at the L3-L4 vertebrae level.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Furthermore, in tests using synthetic spines, a maximum non-destructive axial compression of 350 N is recommended. [31,32] Accordingly, we chose 325 N which corresponded to a 3 mm displacement. The first set of experiments were carried out using a synthetic biomimetic lumbar spine model (Sawbones, WA, USA) at the L3-L4 vertebrae level.…”
Section: Resultsmentioning
confidence: 99%
“…Upward and backward traction not only makes the bone fragments continue to be restored upward, but also makes the bone fragments displaced forward and downward return upward and backward [8]. The author's research based on his finite element model of burst fracture shows that it is safe to implant pedicle screw oblique downward within 15 degrees [19,21].…”
Section: Mechanism and Advantage Of Traction Reduction Of Oblique Dow...mentioning
confidence: 99%
“…The author's series of studies on the treatment of thoracolumbar fractures with short-segment pedicle screw fixation since 2018 showed that [8,12,18,19,21]: the maximum stress of pedicle screws increased with the aggravation of fracture degree, and the increase of screw stress in forward flexion was the most obvious. In moderate thoracolumbar fracture (LSC score 4-6), the risk of screw breakage is low with both types of screws, so brace assistance is not required.…”
Section: Thoracolumbosacral Orthosis (Tlso)mentioning
confidence: 99%
“…Four previous study models were referenced to generate the fractured spine model [32,[34][35][36]. Each study conducted a comparative analysis according to the screw type, fracture level, and CS screw insertion angle.…”
Section: Spinal Fracturementioning
confidence: 99%